2012
DOI: 10.1164/rccm.201206-0982oc
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Dysfunction and Lipid Accumulation in the Human Diaphragm during Mechanical Ventilation

Abstract: Our data suggest that mitochondrial dysfunction lies at the nexus between oxidative stress and the impaired diaphragmatic contractility that develops during MV. Energy substrate oversupply relative to demand, resulting from diaphragmatic inactivity during MV, could play an important role in this process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
168
3
4

Year Published

2013
2013
2019
2019

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 185 publications
(186 citation statements)
references
References 62 publications
(73 reference statements)
11
168
3
4
Order By: Relevance
“…In vivo, administration of a mitochondria-targeted antioxidant molecule (SS-31) reduced mitochondrial ROSemitting potential by 50% in rat muscle cells (3) and consequently prevented dietary glucose-induced cellular oxidation of GSH into GSSG and inhibited the development of insulin resistance in a model of high-fat diet (3). Likewise, abolishing mitochondrial ROS release with SS-31 also prevented the activation of the muscle ubiquitin-proteasome atrophy pathway in a rat model of diaphragm disuse (119); similar results were obtained by overexpression of the endogenous mitochondrial antioxidant enzyme peroxiredoxin 3 (PRX3) in mice (114). Furthermore, hypertriglyceridemia-induced mitochondrial ROS production in the hypothalamus was found to alter cellular oxidative stress and signal satiety, such that blocking this mitochondrial signal with antioxidants prevented satiety in rats and increased calorie intake (9).…”
Section: R399 Mitochondrial Morphology and Functionmentioning
confidence: 73%
“…In vivo, administration of a mitochondria-targeted antioxidant molecule (SS-31) reduced mitochondrial ROSemitting potential by 50% in rat muscle cells (3) and consequently prevented dietary glucose-induced cellular oxidation of GSH into GSSG and inhibited the development of insulin resistance in a model of high-fat diet (3). Likewise, abolishing mitochondrial ROS release with SS-31 also prevented the activation of the muscle ubiquitin-proteasome atrophy pathway in a rat model of diaphragm disuse (119); similar results were obtained by overexpression of the endogenous mitochondrial antioxidant enzyme peroxiredoxin 3 (PRX3) in mice (114). Furthermore, hypertriglyceridemia-induced mitochondrial ROS production in the hypothalamus was found to alter cellular oxidative stress and signal satiety, such that blocking this mitochondrial signal with antioxidants prevented satiety in rats and increased calorie intake (9).…”
Section: R399 Mitochondrial Morphology and Functionmentioning
confidence: 73%
“…Moreover, the activities of the electron transport chain complexes II, III, and IV are depressed in mitochondria isolated from diaphragms of rats exposed to only 12 h of MV and prolonged MV in rats also promotes diaphragmatic mitochondrial uncoupling as indicated by a decrease in the respiratory control ratio (50). Importantly, two independent studies have confirmed that prolonged MV also results in mitochondrial damage in the human diaphragm (80,106). Finally, treatment of animals with a mitochondrialtargeted antioxidant prevents the MV-induced activation of several proteolytic systems and prevents VIDD (82).…”
Section: R468mentioning
confidence: 91%
“…The precise pathways involved in MV-induced diaphragm weakness remain partially understood. Animal models suggest that oxidative stress plays a major role in VIDD (7,8) and recent studies have identified mitochondria as an essential source of reactive oxygen species (ROS) implicated in VIDD (9,10). ROS production is linked to activation of proteolytic systems such as caspases and calpains (11), which play significant roles in degrading cytoskeletal proteins in muscle (6,12,13) directly involved in the development of MVinduced diaphragm muscle fiber atrophy and injury (7,14,15).…”
mentioning
confidence: 99%